Blind spots on the map of aid allocations: Concentration and complementarity of international NGO aid - Dirk-Jan Koch (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The budgets of development NGOs have risen dramatically over the last decades. In stark contrast to bilateral donors, the geographic choices of NGOs remain virtually unexplored. Using a new dataset and Lorenz curves, this paper shows that NGOs are very active in some countries and hardly active in others. A clustering of NGO activity takes place in UN-labelled high priority countries, but ample room for improved targeting exists. Aid concentration curves provide insight into whether NGOs target the same countries as bilateral donors. The article concludes that this is the case and that NGOs are thus acting as complements. The drawback of this complementary approach is that it reinforces the donor darling/donor orphan divide. The paper concludes with some research suggestions and preliminary policy implications.
Keywords: O20; 330; aid allocation; NGO; aid effectiveness; new geographical economics; donor darling; Nichtregierungsorganisation; Entwicklungsplanung; Neue ökonomische Geographie